Theory and method in higher education research. Volume 9 - Huisman, Jeroen; Tight, Malcolm (Theory and method in higher education research, 2023)
Higher education research is a developing field internationally, which is attracting more and more researchers from a great variety of disciplinary backgrounds within and beyond higher education institutions. As such, it is an arena within which a wide range of theories, methods and methodologies is being applied. This volume of Theory and Method in Higher Education Research explores theories such as student development theory, critical race theory applied to international students, critical language theory and linguistic approaches to higher education research. Additionally, methodological contributions include chapters on quasi-experimental methods, arts-based research and reflective dialogues. Including contributors from Sweden, Finland, Japan, the US, and the UK, the chapter authors present international perspectives on the application and development of theory and methodology in researching higher education.